MENINGKATKAN MINAT BELAJAR SISWA SD DALAM PELAJARAN IPAS MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Nuri Maulidatul Hasanah; Septiana Roihanatus Sholihah; Tuhfatul Habibah (Kampus Akademik Publiser, 2025)
Natural and Social Sciences (IPAS) lessons in primary school aims to develop students' scientific and social skills, as well as foster a love of nature. However, students' interest in learning in this subject is still relatively low because it is considered difficult and abstract. Several factors, such as less varied learning methods and interference with gadget use, also influence this condition. This research aims to increase students' interest in learning at SD Negeri Bulay 2 Pamekasan through a contextual approach, which connects the material with students' daily lives. Qualitative research methods were used with the research subjects being teachers and fourth grade students. Data was collected through interviews and closed questionnaires which included indicators of student interest in learning. The research results showed that applying a contextual approach can increase students' interest and understanding of science material. The majority of students show greater interest in learning that is relevant to their daily experiences, especially through practical activities and experiments. This study concluded that the contextual approach is effective in increasing students' interest and active participation in science learning. Recommendations are given to teachers to use varied approaches to create more interactive and interesting learning for students. The abstract is to be in fully-justified text after the Indonesia. Abstract with single column as it is here.